The Nutritional Content Found in Rhizophora Mangrove Fruits in Sondaken Village, Tatapaan Subdistrict, South Minahasa - Mongdong, Priskila Indah Theresya; Mokosuli, Yermia S.; Ogi, Nova L.I.M (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Mangroves are fertile plants that dominate the coastal areas. The fruit of the Rhizophora mangrove can be used as food and beverage ingredients, containing numerous nutrients for the human body. The mangrove fruit contains carbohydrates, water, protein, fat, as well as secondary metabolites such as flavonoids, triterpenoids, tannins, and saponins. The aim of this research is to determine the nutritional content of the Rhizophora apiculata, Rhizophora mucronata, and Rhizophora stylosa mangrove fruits in Sondaken Village, Tatapaan Subdistrict, South Minahasa. This study employs a descriptive research method, where laboratory experiments were conducted using the SNI 01-2891-1992 method at the Baristand Manado laboratory. The nutritional analysis results for Rhizophora apiculata showed a water content of 62.17%, ash content of 1.09%, protein content of 0.59%, fat content of 0.79%, crude fiber content of 5.45%, and carbohydrate content of 35.36%. For Rhizophora mucronata, the analysis revealed a water content of 65.54%, ash content of 3.07%, protein content of 1.27%, fat content of 0.74%, crude fiber content of 7.52%, and carbohydrate content of 29.38%. Lastly, Rhizophora stylosa had a water content of 64.77%, ash content of 3.547%, protein content of 1.30%, fat content of 1.63%, crude fiber content of 7.14%, and carbohydrate content of 28.76%. These results indicate that mangrove fruits have numerous benefits and contain valuable nutrients and good nutritional value for the body. By preserving the mangrove ecosystem and utilizing the nutrients found in the fruits and leaves, there is an opportunity to explore their potential as alternative natural remedies